HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PERSONAL HYGIENE MENSTRUASI PADA REMAJA PUTRI DI DENPASAR TAHUN 2022 - Ni Nyoman Deni Witari; Ni Putu Widarini; Nyoman Tri Maryanthi (IAKMI South Tangerang Branch, 2023)
Abstract Background: Menstrual Hygiene Management (MHM) is the management of hygiene and health in women during menstruation. Based on IDHS data, there are still many young women who behave poorly in maintaining cleanliness during menstruation, so it can have negative impacts such as the emergence of diseases in reproductive organs. Objective: Seeing the relationship between knowledge and attitudes with personal menstrual hygiene behaviors in young women in Denpasar. Method: This observational analytic study used a cross-sectional approach and was conducted at public and private high schools in Denpasar from March to June 2022. A total of 140 female adolescents were selected using a two-stage cluster random sampling technique. Data was collected using an online questionnaire via Google Form and analyzed using logistic regression analysis. Result: Knowledge and attitudes have a significant relationship with personal menstrual hygiene behaviors in young women in Denpasar. Compared to those who have good knowledge, young women with less knowledge are 2.72 times more likely to behave badly in relation to menstrual personal hygiene (OR = 2.72; 95% CI: 1.33-5.56). Compared to those with a positive attitude, young women who have a negative attitude are 2.63 times more likely to behave badly in relation to menstrual personal hygiene (OR = 2.63; 95% CI: 1.30–5.34). Conclusion: Knowledge and attitudes have a significant relationship with personal menstrual hygiene behaviors in young women in Denpasar. Researchers recommend holding health education and in-depth material about personal hygiene management during menstruation as an effective effort to improve health status. Keywords: Personal Hygiene, Knowledge, Behavior, Adolescent Women, Attitude Abstrak Latar belakang: Manajemen Kebersihan Menstruasi (MKM) merupakan pengelolaan kebersihan dan kesehatan pada perempuan saat menstruasi. Berdasarkan data SDKI, masih banyak remaja putri berperilaku kurang baik dalam menjaga kebersihan saat menstruasi, sehingga dapat berdampak buruk seperti timbulnya penyakit pada organ reproduksi. Tujuan: Melihat hubungan antara pengetahuan dan sikap dengan perilaku personal hygiene menstruasi pada remaja putri di Denpasar. Metode: Penelitian observasional analitik dengan pendekatan cross sectional dan dilakukan di SMA negeri dan swasta di Denpasar pada bulan Maret-Juni 2022. Sebanyak 140 remaja putri yang dipilih dengan teknik two stages cluster random sampling. Data dikumpulkan menggunakan kuesioner online melalui google formulir dan dianalisis menggunakan analisis regresi logistik. Hasil: Pengetahuan dan sikap memiliki hubungan signifikan dengan perilaku personal hygiene menstruasi pada remaja putri di Denpasar. Dibandingkan dengan yang memiliki pengetahuan baik, remaja putri berpengetahuan kurang berpeluang 2,72 kali berperilaku buruk terkait personal hygiene menstruasi (OR= 2,72; 95% CI: 1,33-5,56). Dibandingkan dengan yang memiliki sikap positif, remaja putri yang memiliki sikap negatif berpeluang 2,63 kali berperilaku buruk terkait personal hygiene menstruasi (OR= 2,63; 95% CI: 1,30-5,34). Kesimpulan: Pengetahuan dan sikap memiliki hubungan signifikan dengan perilaku personal hygiene menstruasi pada remaja putri di Denpasar. Peneliti merekomendasikan untuk mengadakan pendidikan kesehatan serta pendalaman materi tentang manajemen kebersihan diri saat menstruasi sebagai upaya efektif dalam meningkatkan derajat kesehatan. Kata kunci: Kebersihan Diri, Pengetahuan, Perilaku, Remaja Putri, Sikap